The role of intangible resources in shaping the financial potential of high technology enterprises on the example of CD Projekt SA - Perło, Dorota; Arszułowicz, Norbert (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: As a result of economic changes over the last few decades, the structure of enterprise resources has changed significantly. Therefore, their development potential is concentrated on intangible resources. A reflection of these changes is the emergence of the Resource-Based View of the Firm (RBV) which has its roots in the works of scientists such as: J.A. Schumpeter, A. Marshall, or E.H. Chamberlin. The importance of the resource theory is mainly based on the technological potential, people’s knowledge or the improvement of management techniques. Aim: The aim of the article is to propose a method for assessing the strength and direction of the impact of intangible resources on the financial potential of high-tech enterprises. In the article, as a case study, the impact of intangible resources on the financial potential of CD Projekt SA was presented. from the high-technology industry (Section C, subclass 26.20.) in 2011–2019. The choice of the company as the research object was primarily determined by the type of business activity, the high position of the enterprise among the fastest growing companies and a significant share of intangible resources. Results: To achieve the aim of the article, the soft modeling method was used which allows to study the relationship between directly unobservable variables. In the constructed soft model, two unobservable (hidden) variables constituting the internal model were adopted: intangible resources (IR) and financial potential (FP). Hidden variables were defined based on the potential set of indicators (observable variables). Specification of the model of the soft impact of intangible resources on the financial result of high-tech enterprises based on the concept of the resource theory. Identification of the most important variables shaping the intangible resources of high technology enterprises, their impact on the financial potential of enterprises, together with the analysis of the dynamics of changes. Defining proposals for recommendations for high-tech companies based on the results of empirical research.